(untitled) (Itinera, 2013)
Referring to Tadeusz Kantor’s Dead class and the renowned mannequins dragged along the stage by its age-old characters, this essay focuses on the material used to build them, namely wax, investigating its distinctive meaning for aesthetics as a theory of perception.